(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2019)
The objective of the current study was to encapsulate flaxseed oil extracted from finely grounded flaxseed powder and determined for its fatty acids content by GC/FID. Ionotropic gelation method was used to form beads containing 40% flaxseed oil with vitamin E being used as an antioxidant agent. The study employed calcium chloride solution as crosslinking agent with a combination of sodium alginate and salep. The effect of polymer concentrations and calcium chloride concentration on the morphology, entrapment efficiency and oil release was studied. The encapsulation efficiency reached 93.46 ± 0.064% using 0.6% of salep and 2% sodium alginate with 0.3M calcium chloride gelling solution. In SGF medium, the matrix released only about 28.56% of the entrapped flaxseed oil after 2 hours. The rest of the oil then released in the SIF medium, continuing for up to 5 h to release 99.32% of the oil.